Optimalisasi Kinerja Limestone Crusher IIIA (LSC IIIA) Dengan Metode Overall Equipment Effectiveness (OEE) Untuk Memenuhi Target Produksi Limestone Di PT. Semen Padang Kecamatan Lubuk Kilangan, Padang, Sumatera Barat - Nefa Rizki Dian; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Semen Padang uses the open-pit mining method, namely quarry mining is a mining method that is carried out by extracting industiral or industrial mineral deposits. Mining meterial that has been mined will be crushed according to size through the crusher tool. The crusher tool used is a hammer crusher. Each crusher has a capacity of 1300 tons / hou on LSC II, 1500 tons / hour and 1700 tons / hour for LSC IIIA and LSC IIIB, and 2200 tons / hour for LSC IV. This research uses the overall equipment effectiveness method, because overall equipment effectiveness aims to measure whether the equipment is working normally. Overall equipment effectiveness world class standard is 85% with availability standard value 90%, perfomance rate 95%, and quality rate value 99.9%. the Overall equipment effectiveness value on the crusher tool is still very low at 45.216%.So, it needs a decrease in the breakdown value of 59.146% or 1 hours per day, from 2.45 hours per day and standby at 76.209% or to 0,67 hours per day from 2.82 hours per day. So that the value of overall equipment effectiveness increase at a fair rate of 60,089%.The point is that the crusher woks properly. Keywords: Crusher, Overall Equipment Effectiveness, LSC, Hours per day, Mining